PENGARUH TINDAKAN SUPERVISI, MOTIVASI, PROFESIONALISME, LOCUS OF CONTROL, KONFLIK PERAN TERHADAP KEPUASAN KERJA - ERLINA OKTAVIANI; AAN MARLINAH (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2014)
The purpose of this research is to analyze the impact of supervisory action, motivation, professionalism, locus of control, role conflict on job satisfaction of auditors in public accounting firms. This study reports the results of a survey of 103 auditors from 18 public accounting firms. Purposive sampling method is used to define the sample. This study find that the two major elements of supervisory: leadership and mentoring and working conditions; professionalism and locus of control give impact on the job satisfaction. One major elements of supervisory: assignments, motivation and role conflict do not give impact on the job satisfaction.